2004
DOI: 10.1128/mcb.24.23.10479-10491.2004
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Shuttling SR Proteins Npl3p, Gbp2p, and Hrb1p Are Part of the Translating mRNPs, and Npl3p Can Function as a Translational Repressor

Abstract: A major challenge in current molecular biology is to understand how sequential steps in gene expression are coupled. Recently, much attention has been focused on the linkage of transcription, processing, and mRNA export. Here we describe the cytoplasmic rearrangement for shuttling mRNA binding proteins in Saccharomyces cerevisiae during translation. While the bulk of Hrp1p, Nab2p, or Mex67p is not associated with polysome containing mRNAs, significant amounts of the serine/arginine (SR)-type shuttling mRNA bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
126
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 54 publications
5
126
0
Order By: Relevance
“…Hrb1/ Gbp2 associate both with the genes and the growing, unprocessed mRNA transcripts produced from them and remain bound to the mRNA transcripts as part of the messenger RNA-protein complex (mRNP). As shuttling proteins, Hrb1/ Gbp2 remain bound to the transcript during export from the nucleus; they also remain associated with the mRNP during 618 S. W. James et altranslation (Windgassen et al 2004). et al 2014).…”
mentioning
confidence: 99%
“…Hrb1/ Gbp2 associate both with the genes and the growing, unprocessed mRNA transcripts produced from them and remain bound to the mRNA transcripts as part of the messenger RNA-protein complex (mRNP). As shuttling proteins, Hrb1/ Gbp2 remain bound to the transcript during export from the nucleus; they also remain associated with the mRNP during 618 S. W. James et altranslation (Windgassen et al 2004). et al 2014).…”
mentioning
confidence: 99%
“…A recent study has indicated that Dbp5 can function to remodel RNA-protein interactions in vitro because it is able to promote the dissociation of Nab2 from a Nab2-RNA complex (15). Nab2 associates with polyadenylated RNA but is not found associated with polysomes, indicating that it dissociates from poly(A) RNA before translation (21)(22)(23). Additionally, in vivo cross-linking studies have shown that reduced Dbp5 activity correlates with an increase in both Mex67 and Nab2 association with poly(A) RNA in vivo, consistent with the hypothesis that removal of these proteins from RNA is an in vivo function of Dbp5 (15,24).…”
mentioning
confidence: 99%
“…This model suggests that the effects of SR proteins on translation might be regulated by SR protein kinases as well as proteins involved in nuclear reimport. A recent study by Krebber and collaborators showed that the Npl3p protein associates with yeast polysomes (209). Based on genetic experiments, they proposed that Mtr10p, the import receptor for Npl3p, might be involved in a timely regulated release of Npl3p from the polysomes.…”
Section: Phosphorylation Of the Rs Domain Releasesmentioning
confidence: 99%
“…Similar experiments could also be performed for over-expressed Transportin SR, which is the import receptor for the SR proteins. In yeast studies, it was found that Mtr10p (the yeast homologue of Transportin SR) was important for the release of Npl3p (the SR protein homologue) from polysome-associated mRNAs, but the Sky1p (the kinase homologue) was not important (209). It would be of interest to determine how closely the mammalian system mimics the yeast system.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%